Plasma leucocyte elastase concentrations in smokers. Issue 3 (March 1991) - Hind, C R; Joyce, H; Tennent, G A; Pepys, M B; Pride, N B
Abstract : The associations between cigarette smoking, plasma leucocyte elastase concentration, peripheral leucocyte count and FEV1 were examined in 148 men, 72 of whom were current cigarette smokers, 40 of whom were ex-smokers, and 36 who had never smoked. All men were part of a long-term survey. Smokers had significantly higher plasma leucocyte elastase concentrations than ex-smokers or those who had never smoked. Mean current FEV1 was lower, and the annual decline in FEV1 in the preceding 10 years was faster in smokers than the other two groups. A few smokers had slight increases in serum C-reactive protein concentrations. Although peripheral blood leucocyte counts were higher in smokers than in non-smokers or ex-smokers, no association was found in any of the three groups of men between plasma elastase concentration and peripheral leucocyte count, nor between either of these two variables and annual decline in FEV1 or current level of FEV1. There was also no relation between plasma elastase concentration and reported daily cigarette consumption or mixed expired carbon monoxide in smokers. The results indicate that some male smokers have increased in vivo release of elastase from peripheral blood neutrophils at a time when there is no evidence of acute infection. Because leucocyte elastase is a strong candidate for pulmonary tissue damage, further studies of the mechanisms that increase plasma concentrations are indicated.